Do L2 lexical and syntactic accuracy develop in parallel? Accuracy development in L2 Chinese writing. (November 2020) - Liao, Jianling
Abstract: In a departure from the conflated analysis methods used to measure linguistic accuracy in previous studies, the current study provides an independent analysis of L2 Chinese written lexical and syntactic accuracy to test the possibility that they may tap into different linguistic abilities. A range of measures were used to analyze lexical and syntactic accuracy performance and their interrelations in writing. The results show that lexical and syntactic accuracy contribute to L2 accuracy in different and unique ways. Lexical accuracy showed a V-shaped development, regressing in the middle-score group and rebounding in the high-score group. Syntactic accuracy demonstrated a relatively linear development from the low-score to the high-score group. The correlations between lexical and syntactic accuracy decreased with increased proficiency, and specific lexical or syntactic accuracy features displayed differential developmental paths and capacity in distinguishing proficiencies. Highlights: Lexical accuracy showed a V-shaped developmental path. Syntactic accuracy demonstrated a relatively linear development. The correlations between lexical and syntactic accuracy decreased with increased proficiency.